Faktor Yang Mempengaruhi Nilai Perusahaan Pada Perusahan Manufaktur Yang Terdaftar Di BEI - Monica Melvi Reviani, Henryanto Wijaya (Jurnal Paradigma Akuntansi, 2019)
This research aims to examine the effect of profitability, company size, company growth, and leverage to the firm value onmanufacturing companies that listed on Indonesia Stock Exchange for the period of 2015-2017. The samples of this research are sixty fivemanufacturing companies selected using purposive sampling method. The research data has been processed by using EViews 9.0.  The result of this research shows that partially, profitability has a positive andnot significant influence to the firm value, company size has a positive and not significant influence to the firm value, company growth has a positive and not significant influence to the firm value, and leverage has a positive and not significant influence to the firm value